Федір Вовк - про місце в історії української антропології (до 160-річчя від дня народження) - Таран, О. (Народна творчість та етнографія, 2007)
У березні 2007 року минуло 160 років від дня народження визначного вітчизняного українознавця-енциклопедиста Федора Кіндратовича Вовка. In March of 2007 we celebrated 160th anniversary of the famous Ukrainian anthropologist Fedir Vovk, who belongs to the French anthropological school. His work “Anthropological Features of the Ukrainian Folk” is the first and unique book in which the topic of anthropological roots of the Ukrainians is covered so intensively. His research in the areas of ethnography, folklore, archeology, anthropology is well known in Ukraine and abroad. This article is dedicated to the description of Vovk’s anthropological heritage.